2007
DOI: 10.1007/s11222-006-9005-8
|View full text |Cite
|
Sign up to set email alerts
|

Robust mixture modeling using the skew t distribution

Abstract: A finite mixture model using the Student's t distribution has been recognized as a robust extension of normal mixtures. Recently, a mixture of skew normal distributions has been found to be effective in the treatment of heterogeneous data involving asymmetric behaviors across subclasses. In this article, we propose a robust mixture framework based on the skew t distribution to efficiently deal with heavy-tailedness, extra skewness and multimodality in a wide range of settings. Statistical mixture modeling base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(114 citation statements)
references
References 18 publications
1
112
0
1
Order By: Relevance
“…By design, our STNMIX model is computationally faster to fit than the skew t mixture (STMIX) model [3,12,16,17] without sacrificing precision or rigor. Ho et al [13] summarized the differences between the STMIX and STNMIX models and showed the implementation of the STNMIX model is generally much simpler and faster than that of STMIX model.…”
Section: Resultsmentioning
confidence: 99%
“…By design, our STNMIX model is computationally faster to fit than the skew t mixture (STMIX) model [3,12,16,17] without sacrificing precision or rigor. Ho et al [13] summarized the differences between the STMIX and STNMIX models and showed the implementation of the STNMIX model is generally much simpler and faster than that of STMIX model.…”
Section: Resultsmentioning
confidence: 99%
“…This has been shown in terms of density modeling and cluster analysis for multivariate data (Mclachlan and Peel, 1998;Peel and Mclachlan, 2000) as well as for univariate data by using a skewed-t mixture model (Lin et al, 2007). The t-distribution with location parameter µ ∈ R, scale parameter σ 2 ∈ (0, ∞) and degrees of freedom ν ∈ (0, ∞) has the probability density function…”
Section: The T Distributionmentioning
confidence: 93%
“…Lin et al (2007) proposed a mixture of skew t distributions to deal with heavy-tailed and asymmetric distributions. However, in the skew-t mixture model of Lin et al (2007), the mixing proportions and the components means are constant and are not predictor-depending and hence doest not consider the regression problem and is not a mixture of experts model. Wei (2012) considered the t-mixture model for the regression context on univariate data where the means µ k in (13) are (linear) regression functions of the form µ(x; β k ).…”
Section: The T Moe (Tmoe) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the usefulness of the FM models, many kinds of different FM models were introduced in the past decade via considering various mixture components. For example, see the article by Lin et al (2007) and Lin (2010) and monographs by McLachlan and Basford (1988) , Frühwirth-Schnatter (2006).…”
Section: Introductionmentioning
confidence: 99%